Comparative evaluation of bioactive phytochemicals in Spinacia oleracea cultivated under greenhouse and open field conditions - Bum Soo Lee; Hae Min So; Sil Kim; Jung Kyu Kim; Jin-Chul Kim; Dong-Min Kang; Mi-Jeong Ahn; Yoon-Joo Ko; Ki Hyun Kim (대한약학회, 2022)
Various factors related to growing conditions caninfl uence the nutritional quality of plants, including vegetablecrops, especially the contents of health-promotingphytochemicals. In this study, the phytochemical contentsof spinach ( Spinacia oleracea ) cultivated under greenhouseand open fi eld conditions were comparatively analyzed usinga metabolomic approach with Mass Profi ler Professional(MPP) software. S. oleracea , which is one of the well-knownleafy vegetables belonging to the family Chenopodiaceae,is cultivated worldwide. Although the nutritional value ofspinach is high, the phytochemical contents of spinach cultivatedunder greenhouse and open fi eld conditions havenot been comparatively analyzed. Metabolomic analysisof the methanol (MeOH) extracts of greenhouse-cultivatedspinach (GS) and open fi eld-cultivated spinach (OFS) usingultra-high performance liquid chromatography-quadrupoletime-of-fl ight mass spectrometry (UPLC-Q-TOF-MS), followedby principal component analysis (PCA) with MPP demonstrated the diff erential metabolite profi les of GS andOFS. The active compounds 1？3 were isolated and identifi edusing LC-Q-TOF-MS-guided fractionation. Among these,5,3’,4’-trihydroxy-3-methoxy-6,7-methylenedioxyfl avone4’-glucuronide (2) exhibited growth-inhibitory activitiesagainst Helicobacter pylori 51. Distribution analysis ofcompound 2 revealed that the anti- H. pylori compound 2 isan OFS-specifi c bioactive phytochemical. This indicates thatthe phytochemical quality of OFS is better than that of GS. These fi ndings will aid in providing vital data for vegetableprocessors, dieticians, nutritionists, and consumers to selectoptimal green leafy vegetables.